Training of Culinary MSME in Facing The Digital Era Using Digital Payment Methods and Digital Financial Bookkeeping - Olimsar, Fredy; Afrizal, Afrizal; Yulmardi, Yulmardi; Safelia, Nela; Putra, Dios Nugraha; Sari, Naura Juwita (Pascasarjana Universitas Mataram, 2024)
We are living in a digital age where all sales transactions may be completed online. Based on this, the bare minimum of business owners is those who utilize digital commerce and create digital banking records. Pempek Sohib is a micro, small, and medium enterprise (MSME) in the capital of Jambi. The business owner still primarily uses non-digital methods to make transactions. Due to this, the purpose of this service is to provide guidance and instruction in creating digital currency and payment methods. The devotion will be carried out to provide training and support for business owners. The outcome of this PPM is that MSME business owners may embrace digital transformation by implementing digital payment methods and financial records and increasing the value and quality of their efforts